2019
DOI: 10.1073/pnas.1822026116
|View full text |Cite
|
Sign up to set email alerts
|

Alarmone Ap4A is elevated by aminoglycoside antibiotics and enhances their bactericidal activity

Abstract: Second messenger molecules play important roles in the responses to various stimuli that can determine a cell's fate under stress conditions. Here, we report that lethal concentrations of aminoglycoside antibiotics result in the production of a dinucleotide alarmone metabolite–diadenosine tetraphosphate (Ap4A), which promotes bacterial cell killing by this class of antibiotics. We show that the treatment of Escherichia coli with lethal concentrations of kanamycin (Kan) dramatically increases the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Thus, colistin might be a good candidate for combinational therapy with β-lactam antibiotics to treat A. baumannii infection. This result is also consistent with our previous studies that targeting bacterial persistence or tolerance could highly enhance the antibiotic treatment [27,57].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, colistin might be a good candidate for combinational therapy with β-lactam antibiotics to treat A. baumannii infection. This result is also consistent with our previous studies that targeting bacterial persistence or tolerance could highly enhance the antibiotic treatment [27,57].…”
Section: Discussionsupporting
confidence: 93%
“…We suspected that the genetically encoded ATP sensor can act as a buffer absorbing some of this ATP flux from a loss of translation, while the luminescence-based assay measures absolute values after the cells are permeabilized. This interpretation is consistent with recent results which show an increase in an alarmone with an ATP precursor after aminoglycoside treatment 41 . Collectively these data suggest that there may be a change in metabolic flux in the system, and are consistent with prior observations of aminoglycoside treated cells, which were found to leak NTPs 6 and increase respiration 18 .…”
Section: Atp Dysregulation Precedes Voltage Induced Bactericidal Killsupporting
confidence: 94%
“…Studies on the function of Ap 4 A in Escherichia coli have shown that it may be a damage metabolite and a few proteins binding Ap 4 A in these bacteria were identified [178]. Recent studies on the function of Ap 4 A have shown that aminoglycoside antibiotics induced synthesis of Ap 4 A in Escherichia coli and it caused bacterial cell killing by these antibiotics [179]. Lysyl-tRNA synthetase plays a key role in MITF (microphthalmia-associated transcription factor) transcriptional activity via Ap 4 A as an important signaling molecule in mast cells [180,181].…”
Section: Function Of Uncommon Nucleotidesmentioning
confidence: 99%